If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 8y = 12y Solving 16 + 8y = 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 16 + 8y + -12y = 12y + -12y Combine like terms: 8y + -12y = -4y 16 + -4y = 12y + -12y Combine like terms: 12y + -12y = 0 16 + -4y = 0 Add '-16' to each side of the equation. 16 + -16 + -4y = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -4y = 0 + -16 -4y = 0 + -16 Combine like terms: 0 + -16 = -16 -4y = -16 Divide each side by '-4'. y = 4 Simplifying y = 4
| 3*-14+4*y=12 | | 4(5x+3)=28 | | x-45+150=180 | | -4x-1/3=35/3 | | x+4+132=180 | | (3y+8)=(6y-1) | | 4x-1/3=35/3 | | 6x+(2)(15)=150 | | -5y+6=-7y-14 | | (6x)=(5x+9) | | 8y-3=5(y+6) | | 3x-20=6x-8 | | 10+3y=-6 | | S=Ngj | | 3(2+x)=-36 | | x^2-2400=0 | | -2g-6=-9 | | 360=(6+3w)(w) | | 18+0.5x=25 | | 3(2c-5)+2c= | | -8w-2=-10-4w | | 4x+6-x=22+6 | | -1/3(9s-36t=-5)= | | 24+2X=110 | | -5+3y=-6 | | 5p-2q=3m+d | | -7(x+2y+5z)= | | 11a+b=5a+24 | | 8y=-8+7y | | -10+3y=-6 | | 64-x=156 | | y+1=16-2y+6 |